2020
DOI: 10.1111/pedi.13150
|View full text |Cite
|
Sign up to set email alerts
|

Fear of hypoglycemia in children with type 1 diabetes and their parents: Effect of pump therapy and continuous glucose monitoring with option of low glucose suspend in the CGM TIME trial

Abstract: To determine if pump therapy with continuous glucose monitoring offering low glucose suspend (LGS) decreases fear of hypoglycemia among children with type 1 diabetes and their parents. The CGM TIME trial is a multicenter randomized controlled trial that enrolled 144 children with type 1 diabetes for at least 1 year (mean duration 3.4 ± 3.1 years) starting pump therapy (MiniMed™ Veo™, Medtronic Canada). CGM (MiniMed™ Enlite™ sensor) offering LGS was introduced simultaneously or delayed for 6 months. Hypoglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…As a result, there was a floor effect, which would have impacted results in our study. CGM offering LGS was found to be associated with lower fear of hypoglycemia in participants and their parents as measured by the Hypoglycemia Fear Scare 18 …”
Section: Discussionmentioning
confidence: 95%
“…As a result, there was a floor effect, which would have impacted results in our study. CGM offering LGS was found to be associated with lower fear of hypoglycemia in participants and their parents as measured by the Hypoglycemia Fear Scare 18 …”
Section: Discussionmentioning
confidence: 95%
“…Data on SAP in a pediatric population studying the effect on HbA1c, hypoglycemia and/or QoL, are emerging (10,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(26)(27)(28). Eleven observational studies and five RCTs introducing RT-CGM in pediatric pump users, have been performed from 2010 until mid-2022, including 16 to 622 (of which 129 on SAP) children/adolescents with T1D per study, with a trial duration of 2 to 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical benefits of RT-CGM have been demonstrated in randomized controlled trials (RCTs) before, they often only analyzed 6- or 12-month data or even less ( 10 , 13 19 , 21 , 22 , 24 ), and therefore do not inform about sustainability of its effects. Furthermore, most RCTs do not assess the effect of novel technology on hospitalizations because being hospitalized due to hypoglycemia or ketoacidosis is usually an exclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CGM TIME trial, which involved 144 children with type 1 diabetes for at least 1 year, patients were treated using a sensor‐augmented personal insulin pump with the LGS function, and parents completed the HFS‐II questionnaire at baseline and after 12 months of treatment. The study demonstrated that personal insulin pump therapy with the LGS function significantly reduced the FOH (Verbeeten et al., 2021 ). Another technology used in sensor‐augmented personal insulin pumps predicts drops in glucose levels 30 min before reaching a given value and allows insulin delivery to be automatically suspended and then automatically continued when the downward trend in blood glucose has subsided.…”
Section: Modern Technologies and Fohmentioning
confidence: 99%